2015
DOI: 10.1111/are.12930
|View full text |Cite
|
Sign up to set email alerts
|

Induced spermiation ofPimelodus britskii(Teleostei: Pimelodidae) during the reproductive period

Abstract: For the first time was characterized the semen of Pimelodus britskii, hormonally induced and noninduced induced, during the reproductive period. The experiment 1 was conducted with 12 fish per month, divided into: (i) induced with Carp Pituitary Extract (CPE), and (ii) without hormonal induction (testes macerated). The experiment 2 was conducted, with 30 fish, divided into groups for comparison of different doses of CPE and human Chorionic Gonadotrophin (hCG; T1: control; T2: 3.0 mg kg À1 CPE; T3: 0.5 mg kg + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
(65 reference statements)
0
1
0
4
Order By: Relevance
“…Spermatozoa morphology affects sperm motility and fertilizing capacity (Murgas et al, 2011), and other studies also reported seasonal variations on fish sperm morphology (Damasceno et al, 2015; Kuradomi et al, 2016). In this study, midpiece degeneration was the most observed damage in post‐thaw spermatozoa (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Spermatozoa morphology affects sperm motility and fertilizing capacity (Murgas et al, 2011), and other studies also reported seasonal variations on fish sperm morphology (Damasceno et al, 2015; Kuradomi et al, 2016). In this study, midpiece degeneration was the most observed damage in post‐thaw spermatozoa (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Por esta razón, se presenta una disrupción reproductiva en cautiverio debido a la falta de estímulos ambientales apropiados y que en los machos de Pimelodus spp. se agrava porque los testículos digitiformes [10] impiden que el semen se libere por masaje abdominal durante los procedimientos de reproducción inducida [11]. Por otro lado, la ausencia tanto de maduración final de los ovocitos como de ovulación en pimelodidos en cautiverio, indica que el desove parece estar estrictamente modulado por la síntesis y liberación de LHβ [12].…”
Section: Introductionunclassified
“…Los silúridos, en su mayoría responden positivamente a protocolos de inducción hormonal. Sin embargo, un escaso números de bagres como los Clarias gariepinus (Viveiros et al, 2002), Ictalurus furcatus (Gima et al, 2013), Pimelodus britskii (Damasceno et al, 2015), Leiarius marmoratus (Araújo et al, 2014) y Sorubim y lima (Shibatta et al, 2011) liberan míni-mo volumen seminal mediante estrujamiento manual, comparado con el volumen obtenido directamente de los testículos. Varios factores han sido atribuidos como causa de este fenómeno.…”
Section: Introductionunclassified
“…Varios factores han sido atribuidos como causa de este fenómeno. Según Damasceno et al, (2015), la morfología y ubicación anatómica de los testículos así como el protocolo de inducción hormonal y la fase de la estación reproductiva son determinantes en Pimelodus britskii. Desde otra perspectiva, Araújo et al, (2014), relaciona esta deficiencia en L. marmoratus con la falta de domesticación de los reproductores.…”
Section: Introductionunclassified